(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The agricultural products supply chain has a significant role in the formation and integration of businesses and economic activities of the agricultural sector and food security. The tomato crop in Bushehr faces different challenges reducing the pace of the chain operation of this crop. Thus, the purpose of the study was to determine and weigh the inhibitory risks of tomato crop supply chain development in Bushehr. The designed questionnaire was given to 30 Bushehr Agriculture Jihad Organization experts to collect data and to perform pairwise comparisons of supply chain risk criteria of the tomato crop, and fuzzy analytic hierarchy process (FAHP) was used to weight and prioritize the criteria. The findings indicated that from among the six main criteria, the highest weight was related to environmental risks (0.354) and the lowest to social-service risks (0.029). Additionally, economic, policy-making, technical-infrastructure, and education-extension risks have relative weights of 0.214, 0.145, 0.133, and 0.125, respectively. Thus, planning and investing in improving environmental and economic conditions like market regulation and facilitating the payment of agricultural loans can increase the stability of the tomato supply chain.